2013
DOI: 10.1371/annotation/679017bf-abd5-44ce-9e20-5e7af1cd3468
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Pericytes Derived from Adipose-Derived Stem Cells Protect against Retinal Vasculopathy

Abstract: Background: Retinal vasculopathies, including diabetic retinopathy (DR), threaten the vision of over 100 million people. Retinal pericytes are critical for microvascular control, supporting retinal endothelial cells via direct contact and paracrine mechanisms. With pericyte death or loss, endothelial dysfunction ensues, resulting in hypoxic insult, pathologic angiogenesis, and ultimately blindness. Adipose-derived stem cells (ASCs) differentiate into pericytes, suggesting they may be useful as a protective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Human cells derived from adipose stem cells and expressing αSMA, PDGFRβ and NG2 can protect against diabetic retinopathy in a mouse model, causing revascularisation of the retina after injection which was not achieved by injection of human BM-MSCs [91]. This effect of pericyte injection was enhanced when the cells were pre-treated with TGF-β1.…”
Section: Pericytes As a Therapeutic Agentmentioning
confidence: 99%
“…Human cells derived from adipose stem cells and expressing αSMA, PDGFRβ and NG2 can protect against diabetic retinopathy in a mouse model, causing revascularisation of the retina after injection which was not achieved by injection of human BM-MSCs [91]. This effect of pericyte injection was enhanced when the cells were pre-treated with TGF-β1.…”
Section: Pericytes As a Therapeutic Agentmentioning
confidence: 99%
“…Currently, adipose-derived stromal cells (ASCs) are considered to be the most suitable source of MSCs, mainly due to their highly proliferative activity and immunomodulatory properties, but also due to the safe method of their isolation [17]. Recently, it has been reported that ASCs exhibit a neuroprotective effect by secreting trophic/neuroregulatory factors [17,18]. The pro-regenerative potential of ASCs is explained by their ability to produce and secrete nano- and micro-sized extracellular vehicles (EVs), which include both exosome and microvesicles (MVs) populations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions ASC-derived pericytes adopt pericyte morphology, showing pericyte-specific markers, and their phenotype is enhanced with TGF-β1 treatment demonstrating that ASCs could be used to protect against DR and to treat retinal vascular disease. [133]. Due to the unavailability of human retinal pericytes for transplantation, these cells, that are able to stabilize existing retinal microvasculature, could therefore represent an alternative therapy to the destructive laser treatment of hypoxic retina.…”
Section: Diabetic Retinopathymentioning
confidence: 99%